Development and Shelf Stability of Convenience and Ready to Eat Chicken Meat Powder Incorporated Cookies - Berwal, Raj Kumar; Khanna, Nita; Berwal, Rekha (Journal of Meat Science, 2018)
The study was conducted to develop cookies incorporated with chicken meat powder (CMP) at 10 to 50 per cent level. On the basis of sensory evaluation, the optimum level of CMP to be incorporated in cookies was selected. Of the various levels of CMP tried; the cookies with 40% CMP were preferred the most. The chicken meat powder incorporated cookies had better appearance, taste, texture, flavour and overall acceptability. It was concluded that the cookies with 40% chicken meat powder and 60% refined wheat flour are ready to eat food, would provide a nutritious diet and could be stored for 90 days at ambient temperature without any significant deterioration in microbiological quality and with acceptable sensory attributes.